Litigating labour: Condoning unreasonable risk-taking in childbirth?. (March 2015) - Heywood, Rob
Given the vast quantity of obstetric litigation and all its associated complexities, in 2012 the National Health Service Litigation Authority (NHSLA) produced a report entitled Ten Years of Maternity Claims: An Analysis of NHS Litigation Authority Data (the 2012 Report). This document identified, inter alia, a number of problematic areas in respect of litigation trends and illuminated a range of clinical situations in which claims are most likely to arise. It is against this backdrop that this paper seeks to critically analyse a body of case law that has occurred since the publication of the 2012 Report. Focusing on breach of duty, the paper seeks to evaluate whether or not the weighing of risks and benefits, as advocated in the case of Bolitho as a means of assessing the question of breach, has been appropriately utilised by judges in recent childbirth cases. It is an important and original piece of research as it is the first of its kind to investigate how judges have dealt with specific aspects of childbirth identified as being contentious in the wake of the 2012 Report.